2016
DOI: 10.1016/j.actamat.2015.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Improving aluminum particle reactivity by annealing and quenching treatments: Synchrotron X-ray diffraction analysis of strain

Abstract: In bulk material processing, annealing and quenching metals such as aluminum (Al) can relieve residual stress and improve mechanical properties. On a single particle level, affecting mechanical properties may also affect Al particle reactivity. This study examines the effect of annealing and quenching on the strain of Al particles and the corresponding reactivity of aluminum and copper oxide (CuO) composites. Micron-sized Al particles were annealed and quenched according to treatments designed to affect Al mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…The Al was then combined with CuO after thermal treatment to assess reactivity. They found that energy propagation for the 100 and 200 °C treatments did not significantly differ from the untreated case, but the 300 °C treatment showed an increase in energy propagation by 24% [20]. These findings were coupled with synchrotron X-ray diffraction (XRD) measurements to quantify particle strain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Al was then combined with CuO after thermal treatment to assess reactivity. They found that energy propagation for the 100 and 200 °C treatments did not significantly differ from the untreated case, but the 300 °C treatment showed an increase in energy propagation by 24% [20]. These findings were coupled with synchrotron X-ray diffraction (XRD) measurements to quantify particle strain.…”
Section: Introductionmentioning
confidence: 99%
“…To gain a better understanding of the effects of annealing µAl particles separately from annealing composites, McCollum et al subjected µAl to a variety of thermal treatments (100, 200 and 300 °C) with one quench rate [20]. The Al was then combined with CuO after thermal treatment to assess reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Particle size response to annealing and quenching treatment is characterized in [15,16] showing no significant deviation in average particle diameter with annealing and quenching treatment.…”
Section: Ii1 Sample Preparationmentioning
confidence: 99%
“…We have detailed the use of this instrumentation for strain measurements on thermally treated Al particles in our previous work [15,16] but the method is summarized here for completeness. Aluminum powder samples were spread over glass slides and scanned under the x-ray beam (either polychromatic or monochromatic) while a diffraction pattern was collected at each step using a DECTRIS Pilatus 1 M detector.…”
Section: Ii2 Strain Measurementsmentioning
confidence: 99%
See 1 more Smart Citation